2010
DOI: 10.1364/oe.18.004673
|View full text |Cite
|
Sign up to set email alerts
|

Multi-mode to single-mode conversion in a 61 port Photonic Lantern

Abstract: Efficient multi-mode (MM) to single-mode (SM) conversion in a 61 port splitter or "Photonic Lantern" is demonstrated. The coupling loss from a 100 µm core diameter MM section to an ensemble of 61 SM fibers and back to another 100 µm core MM section is measured to be as low as 0.76 dB. This demonstration shows the feasibility of using the Photonic Lanterns within the field of astrophotonics for coupling MM star-light to an ensemble of SM fibers in order to perform fiber Bragg grating based spectral filtering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 6 publications
0
57
0
Order By: Relevance
“…So far in published results, photonic lantern core geometries have consisted of hexagonal lattices, rounded array or square lattices with the number of cores approximately equal to the number of final waveguide modes as required [12,13,[17][18][19]. However, it has been theoretically demonstrated that the best starting point for a low loss lantern design is an uncoupled core geometry that best approximates or samples the geometry of the modes of the final MM fiber [14,20,21].…”
Section: Optimum Waveguide Geometrymentioning
confidence: 99%
“…So far in published results, photonic lantern core geometries have consisted of hexagonal lattices, rounded array or square lattices with the number of cores approximately equal to the number of final waveguide modes as required [12,13,[17][18][19]. However, it has been theoretically demonstrated that the best starting point for a low loss lantern design is an uncoupled core geometry that best approximates or samples the geometry of the modes of the final MM fiber [14,20,21].…”
Section: Optimum Waveguide Geometrymentioning
confidence: 99%
“…This is somewhat smaller than ideal given the typical seeing at the site however budget and timescale constraints limited the size of the photonic lanterns that could be considered at the time. Photonic lanterns with 61 SMFs, which would allow 1.8× the AΩ per fibre, have already been demonstrated 7 and developments in multicore fibre and integrated optics photonic lanterns promise to make large values of N readily achievable [8][9][10] in the near future. A spectrograph designed for FBG OH suppression should have collimator and camera optics with sufficiently fast focal ratios to accommodate the beam angles associated with the maximum AΩ values of the photonic lanterns it will be used with.…”
Section: Dark Currentmentioning
confidence: 99%
“…Each input wavelength has a unique fringe representation, which is the basis of the Fourier-transform relation between the input spectra and the output interferogram. Employing multiple input waveguides in the waveguide SHS is an important advantage over the existing AWG-type spectrometer, since it greatly increases the light-capturing capability in proportion to the number of MZIs by using, for example, photonic lantern technology [27]. A photonic lantern is a device that efficiently converts light from a multimode fiber tip for light capturing to single-mode fibers connected to MZI input waveguides.…”
Section: Planar Ft Spectrometermentioning
confidence: 99%